2017
DOI: 10.1002/pssr.201600448
|View full text |Cite
|
Sign up to set email alerts
|

A novel source of atomic hydrogen for passivation of defects in silicon

Abstract: Palladium membranes have been used for decades for the separation of hydrogen from other gasses. In this letter the use of thin palladium leaves to act as sources of atomic hydrogen for silicon samples is explored. It has been assumed in the past that although hydrogen diffuses through palladium in atomic form, the atoms recombine to form molecular hydrogen at the surface. In this letter it is shown that hydrogen supplied to one surface of a palladium leaf can result in atomic hydrogen being released from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…They observed 2–12 times higher SRV and attributed it to the increased surface area, dangling bonds and stress‐induced defects . Most recently, Hamer et al and Bourret‐Sicotte et al reported a new methodology to extrinsically introduce H species into a SiO 2 film using a shielded ammonia plasma. By combining extrinsic chemical and FEP of SiO 2 they successfully achieved τ eff = 6.4 ms, S eff = 0.17 cm s −1 , in n‐type Si 1 Ωcm.…”
Section: Materials and Methods For Silicon Surface Passivationmentioning
confidence: 99%
“…They observed 2–12 times higher SRV and attributed it to the increased surface area, dangling bonds and stress‐induced defects . Most recently, Hamer et al and Bourret‐Sicotte et al reported a new methodology to extrinsically introduce H species into a SiO 2 film using a shielded ammonia plasma. By combining extrinsic chemical and FEP of SiO 2 they successfully achieved τ eff = 6.4 ms, S eff = 0.17 cm s −1 , in n‐type Si 1 Ωcm.…”
Section: Materials and Methods For Silicon Surface Passivationmentioning
confidence: 99%
“…With the development of high-quality room temperature passivation schemes such as SA-treated silicon, low-temperature gettering and hydrogenation techniques can be developed [18]- [21], which otherwise would be difficult to measure, if, for example, these methods relied on SiN x and Al 2 O 3 passivation, which in themselves can introduce hydrogen or change bulk properties through annealing procedures to activate the surface passivation (i.e., 400°C) [44]- [46]. In this regard, the SA treatment can provide valuable information regarding passivation quality of dielectric films and their impact on the bulk material.…”
Section: E Prospects For Superacid-treated Silicon: Applications Formentioning
confidence: 99%
“…By this procedure, an upper limit S of 3 and 13 cm/s on n-and p-type silicon are achieved, respectively [17]. From all these recent studies, it is evident that organic films can provide exceptional silicon surface passivation at very low temperatures (< 200°C), which could open up other opportunities for new and innovative low-temperature gettering and hydrogenation techniques to improve low-quality silicon for their inclusion as the base material in highly efficient solar cells [18]- [21]. However, the level of surface passivation demonstrated until now (>1 cm/s) is not good enough to compete with state-of-the-art dielectric films.…”
mentioning
confidence: 99%
“…In a recent letter, Shielded Hydrogen Passivation (SHP) was introduced as an alternative method for introducing significant amounts of atomic hydrogen at low temperatures . The approach uses plasma, in this case produced within a PECVD machine, to generate atomic hydrogen with a metal shield placed between the sample and the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…In light of these studies and theoretical modelling, it has been assumed that there is a high energy barrier for the release of atomic hydrogen such that it may only occur in the presence of an additional stimulus. However, previous SHP work using Pd leaf has clearly demonstrated that a significant quantity of atomic hydrogen is released from the surface of the leaf opposite the plasma, after which it is detected by diffusion into adjacent Si material. Similar results are presented in this work.…”
Section: Introductionmentioning
confidence: 99%